Digital Smart Marketing: Membangun UMKM Tangguh di Era Ekonomi Digital 5.0 - Enrico Aziezy; Heru Cahyo; Wisnu Wijayanto; Zhika Vilanti; Florenkias Nikosal (Politeknik Negeri Cilacap, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening the local economy of Sunyalangu Village, Karanglewas District, Banyumas Regency. However, most MSMEs still face limitations in utilizing digital technology, particularly in marketing, business administration, and transaction management. This community service activity, titled